(untitled) (Journal of Misan Researches, 2023)
Poverty is a result of the serious basic problems that the Iraqi people have suffered from for many decades. The continuous wars and economic blockade that the Iraqi people suffered from throughout the nineties led to the spread of poverty in Iraq, which led to a significant deterioration of the social and economic infrastructure, its repercussions were dangerous for the Iraqi individual. After 2003 and following the collapse of the totalitarian regime in Iraq, the situation worsened and poverty rates increased as a result of many factors, the most important of which are quotas, terrorism, unemployment, and the interruption of operational structures due to the bad economic policies of successive governments and bad management and distribution of natural resources in Iraq, and the transformation of Iraq as a result of it into a state A rentier dependent on oil alone. Successive governments have tried to develop strategies to reduce the phenomenon of poverty, according to reform policies that ranged between programs and plans.